2017
DOI: 10.4236/wja.2017.71005
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers to Uptake of Voluntary Medical Male Circumcision in a Traditionally Circumcising Community in Machinga District, Malawi

Abstract: Introduction: Voluntary medical male circumcision (VMMC) reduces chances of contracting HIV during heterosexual intercourse in males, and risk of cervical cancer in their female sexual partners. However, its uptake among traditionally circumcising communities, where male circumcision carries a cultural significance, has not been studied. Previous research has focused on barriers to uptake of VMMC in non-circumcising communities. This study was conducted to determine socio-cultural barriers to VMMC uptake in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…These findings are consistent with the results of a qualitative study conducted in Botswana which revealed that older men were not comfortable being addressed by youth on male circumcision (Sabone et al, 2013 ). This study, therefore, recommends the provision of gender-and-culture sensitive VMMC to remove the barriers of the uptake of VMMC among men in Botswana (Masese, Chimango, & Mbirimtengerenji, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results of a qualitative study conducted in Botswana which revealed that older men were not comfortable being addressed by youth on male circumcision (Sabone et al, 2013 ). This study, therefore, recommends the provision of gender-and-culture sensitive VMMC to remove the barriers of the uptake of VMMC among men in Botswana (Masese, Chimango, & Mbirimtengerenji, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support the important role of women as significant social support systems in influencing men to undergo male circumcision [3, 4, 7, 8, 13 & 15]. These studies and various other studies and literature led the researchers to conduct the study to develop a women empowerment framework focusing on women as the recipients of VMMC information and influencers in promoting VMMC uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to men seeking circumcision include fear of pain, myths and misconceptions about infertility following circumcision. Some of the men perceived themselves as not being susceptible to HIV hence seeing no need to undergo the procedure while others who were not aware of their HIV status had fear of being tested for HIV as a barrier to VMMC uptake [2, 3]. Deterrents to VMMC such as lack of partner, parent or social support emerged in support of these factors [4].…”
Section: Introductionmentioning
confidence: 99%
“…The coverage showed substantial increases from 85.0% in 2007 to 91.2% in 2012 in priority countries, although it is still beyond the national target in traditionally non‐circumcising communities (Davis et al., 2018). Fear of pain, bleeding, perception of low HIV risk, lack of social support, presence of female providers on the circumcision team and a preference for traditional ‘rite of passage’ circumcision are important barriers to the uptake and scaling‐up of this intervention (Masese, Chimango, & Mbirimtengerenji, 2017). Health authorities should collaborate with traditional circumcisers and local leaders to provide safer, gender‐and‐culture‐sensitive medical male circumcision services.…”
Section: Discussionmentioning
confidence: 99%